Effects of different protein to carbohydrate ratio in pellets for rearing European cuttlefish (Sepia officinalis, Linnaeus 1758) juveniles - Coriel, Nuno Dias Pinheiro Valadas (2020)
Being highly sought-after fishery resources, cephalopods potential for aquaculture has been a research topic for several decades. The diversity within the class means that each species has its own unique requirements under a culture environment, this poses a great obstacle to overcome. One of these bottlenecks is achieving a nutritional balance in artificial diets which promotes growth, welfare and directly influences the economic viability of cephalopod culture. In this study, which is part of the Sepiacul project, three different artificial diets were tested, each containing different protein to carbohydrate ratios (55:10, 51:15 and 47:20). These diets were tested on Sepia officinalis, against a control group, which was fed frozen grass shrimp (Palaemonetes varians). Cuttlefish used were reared in an open-water system, in the Ramalhete (Ria Formosa, South of Portugal – 37º00′22.39″N; 7º58′02.69″W) pilot station. Pelleted diets did not promote growth and even caused weight loss, resulting in negative absolute and specific growth rates and feeding efficiency. Artificial diets were accepted on day 1 in all treatments, however, cannibalism started occurring by the end of the trials second week, forcing trial shut down. Histology analysis was performed by removing the digestive gland and processing it. Afterwards four different parameters were studied to determine differences between treatments in the digestive gland: existence of structural damage; cell organization; presence of select structures; existence of carbohydrate/glycogen clusters. No difference was found between artificial diet treatments and control (p > 0.05). However, digestive gland index was found to have a significant difference between pelleted treatments and control (p < 0.05), with control digestive glands weighing far more than the pelleted diet counterparts. One of the factors that is believed caused artificial diets not to promote growth is related to raw material processing, more specifically the protein portion.